Learning to Overcome a Lack of Evolutionary History: Can an Endangered Fish Learn to Fear an Introduced Predator? - Farnsley, Sarah; Kuhajda, Bernard; George, Anna; Klug, Hope (Frontiers in Ecology and Evolution, 2018)
Rapid environmental change has led to unprecedented rates of biodiversity loss. One source of rapid environmental change involves the introduction of non-native species. In many cases, lack of evolutionary history with introduced species means that native species lack adaptive responses to avoid predation by introduced species. Understanding how native species can persist with introduced species has been a major focus of biological research. In some cases, learning can allow native individuals to acclimate when faced with introduced species. However, we lack a comprehensive understanding of whether learning can allow individuals to overcome a lack of evolutionarily engrained behavior in relation to non-native species. Here, we illustrate that in some cases individuals can potentially learn to overcome a lack of evolutionarily engrained anti-predator behavior when faced with a novel predator and be conditioned to avoid predation. Specifically, by pairing an aversive stimulus with the presence of an introduced, novel fish predator and measuring behavioral and survival effects, we demonstrate that an endangered fish species, the Barrens Topminnow (BTM), Fundulus julisia, can learn to exhibit anti-predator behavior toward an introduced predator. This anti-predator behavior potentially increases survival in the wild. In addition, our findings suggest that BTM adjust their behavior in response to chondroitin sulfate, suggesting that this chemical might function as an alarm cue in this species.